Apelin promotes lymphangiogenesis and lymph node metastasis - Berta, Judit (Impact Journals LLC, 2014)
Whereas the role of the G-protein-coupled APJ receptor and its ligand, apelin, in angiogenesis has been well documented, the ability of the apelin/APJ system to induce lymphangiogenesis and lymphatic metastasis has been largely unexplored. To this end, we first show that APJ is expressed in lymphatic endothelial cells (LECs) and, moreover, that it responds to apelin by activating the apelinergic signaling cascade. We find that although apelin treatment does not influence the proliferation of LECs in vitro, it enhances their migration, protects them against UV irradiation-induced apoptosis, increases their spheroid numbers in 3D culture, stimulates their in vitro capillary-like tube formation and, furthermore, promotes the invasive growth of lymphatic microvessels in vivo in the matrigel plug assay. We also demonstrate that apelin overexpression in malignant cells is associated with accelerated in vivo tumor growth and with increased intratumoral lymphangiogenesis and lymph node metastasis. These results indicate that apelin induces lymphangiogenesis and, accordingly, plays an important role in lymphatic tumor progression. Our study does not only reveal apelin as a novel lymphangiogenic factor but might also open the door for the development of novel anticancer therapies targeting lymphangiogenesis.